2014
DOI: 10.1039/c3gc41997e
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of 27 pyrrolidinium, morpholinium, piperidinium, imidazolium and pyridinium ionic liquid cations under aerobic conditions

Abstract: The chemical and thermal stability of ionic liquids (ILs) makes them interesting for a large variety of applications in nearly all areas of the chemical industry. However, this stability is often reflected in their recalcitrance towards biodegradation, which comes with the risk of persistence when they are released into the environment. In this study we carried out a systematic investigation of the biodegradability of pyrrolidinium, morpholinium, piperidinium, imidazolium and pyridinium-based IL cations substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 65 publications
7
123
0
2
Order By: Relevance
“…The solubility test was conducted using popular solvents according to the method described by Vogel. 41 The results are presented in Table 2. ILs were insoluble in water, acetone and acetonitrile, soluble in methanol, chloroform and moderately in toluene.…”
Section: 40mentioning
confidence: 99%
“…The solubility test was conducted using popular solvents according to the method described by Vogel. 41 The results are presented in Table 2. ILs were insoluble in water, acetone and acetonitrile, soluble in methanol, chloroform and moderately in toluene.…”
Section: 40mentioning
confidence: 99%
“…In soils, Modelli et al (2008), demonstrated that at the end of a 180-day respirometric experiment, none of the four imidazolium-based ILs was mineralized completely, and the amount of evolved CO 2 depended on both the type of cation and the type of anion. Primary biodegradation, defined as an "alteration in the chemical structure of a substance, brought about by biological action, resulting in the loss of a specific property of that substance" (OECD, 301, 1992) of imidazolium-, morpholinium-, piperidinium-, pyridinium-and pyrrolidiniumbased ILs, has been studied Neumann et al, 2014) and formation of biotransformation products of some imidazolium-and pyridinium-based ILs documented Pham et al, 2009;Docherty et al, 2010). Sorption of ILs onto the soil matrix can occur, depending on soil parameters (such as organic carbon content or cation exchange capacity), which can lead to a decrease of their bioavailability and biodegradability and contribute to the potential persistence (Stepnowski, 2005;Studzi nska et al, 2008;Mrozik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(EsquivelViveros et al, 2009) and also Sphingomonas paucimobilis (Abrusci et al, 2011) and Kocuria palustris (Megaw et al, 2013). When metabolites have been analysed from biodegradation of the related cation [C 8 mim] by microbial communities, evidence has suggested that terminal oxidation of the side chain had taken place (Neumann et al, 2014). An analysis of metabolites after biodegradation of >, 1 mM.…”
Section: Effect Of Il On Reactive Oxygen Species (Ros)mentioning
confidence: 95%
“…Previous studies by Stolte's group (Neumann et al, 2014) have indicated that alkyl side-chains can be degraded by microbial communities via oxidative processes. While the imidazolium ring itself generally exhibits high stability towards biodegradation, in common with the organisms in Stolte's studies, S. quadricauda may be able to oxidise the ring's butyl side-chain and use its carbon as a food source, resulting in a higher metabolic rate.…”
Section: Inhibition Of Esterase Activitymentioning
confidence: 99%